The Lazarus life : spiritual transformation for ordinary people - Smith, Stephen W., 1954- (Colorado Springs, CO : David C. Cook, 2008)
Stephen W. Smith takes a profound walk through the life of Lazarus, a story that offers remarkable insights into our own spiritual transformation.
I am Lazarus : finding ourselves in the story -- The lingering Jesus : waiting for his presence -- Trapped in the tomb : when life comes to a dead end -- The voice of love : hearing your savior call you by name -- The stench of transformation : the messy realities of spiritual change -- Stepping toward life : choosing to stumble out of darkness -- Naming the graveclothes : recognizing the things that bind you -- Removing the graveclothes : embracing the help of a loving community -- Living in the light : the power of our transformation -- The Lazarus life : experiencing transformation for a lifetime.
Includes bibliographical references.
Keywords: Spiritual formation; Raising of Lazarus (Miracle)